FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN TRANSPORTASI ONLINE DI KOTA BANDA ACEH - Dina Karina; Srinita Srinita (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThis study aims to analyse the factors that could affect the demand of online transportation in Banda Aceh. This study use primary data which are obtained from questionnaires to online transportation users. The samples of this study are a hundred of online transportation user. Meanwhile, this study applied multiple linear regression. There are four independent variables that influence the dependent variables, they are; income, price, promotion, and services. Based on the regression results, variable of income and price give the negative and significant effect while the promotion and services variables significantly influence the demand of online transportation. This study inform us that promotion and services by online transportation can increase a demand of online transporation. A good services can attract people to use online transportation, it means that if online transportation give a good service to users it will make them use online transportation for the next day. Most people only use online transportation if they are getting a promotion, 58 percent said that the promotion was very profitable for consumers, 30 percent said they agreed, and only 12 percent said they disagreed.Keywords: Banda Aceh city, Online Transportation, Promotion, Service